2005
DOI: 10.1128/jvi.79.15.9449-9457.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Lymphotropic Virus Type 1 Mitochondrion-Localizing Protein p13 II Sensitizes Jurkat T Cells to Ras-Mediated Apoptosis

Abstract: II 's influence on lymphocyte survival. Our data are the first to demonstrate that p13 II alters Ras-mediated apoptosis in T lymphocytes, and they reveal a potential mechanism by which HTLV-1 alters lymphocyte proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
(40 reference statements)
2
36
0
Order By: Relevance
“…induced by ceramide and FasL [17,18]. These findings are consistent with the hypothesis that p13 may act by lowering the threshold of PTP opening, as observed in isolated mitochondria.…”
Section: Effects Of P13 On Cell Turnover and Transformationsupporting
confidence: 90%
“…induced by ceramide and FasL [17,18]. These findings are consistent with the hypothesis that p13 may act by lowering the threshold of PTP opening, as observed in isolated mitochondria.…”
Section: Effects Of P13 On Cell Turnover and Transformationsupporting
confidence: 90%
“…[31][32][33] Furthermore, the p13 protein has been reported to suppress cell growth in vitro, tumorigenicity in vivo, and to sensitize Jurkat T cells to Ras-mediated apoptosis. 34,35 In the present study, we describe a novel function for p13, demonstrating that it is a negative regulator of HTLV-1 replication in the presence of Tax. The p13 protein binds to Tax and interferes with Tax-CBP/ p300 complex formation, thereby decreasing Tax transcriptional activity.…”
Section: Introductionmentioning
confidence: 68%
“…Studies of p13 II have focused primarily on its biochemical properties (11) and in vitro functions, such as suppression of cell proliferation (38) and sensitization to Ras-dependent apop- (19). In addition, we showed that expression of p13 II in HeLa cells was associated with a significant suppression of the tumorigenicity of c-myc-and Ha-rascotransfected rat embryonal fibroblasts in a nude mouse model (12,38).…”
Section: Discussionmentioning
confidence: 87%
“…p13 II localizes and accumulates in the inner membranes of mitochondria, and when ectopically expressed, it causes alteration of mitochondrial morphology and function (7,12). We recently reported the suppressive effect of p13 II on both cell growth in vitro and tumorigenicity in a murine model (12,38) and the sensitization of lymphocytes to apoptosis in a Ras-dependent fashion (19). Collectively, these observations indicate a distinct role for p13 II in HTLV-1 infection and a potential role in HTLV-1-mediated lymphocyte transformation.…”
mentioning
confidence: 99%